2020
DOI: 10.1002/1878-0261.12747
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a combined hypoxia and immune index for triple‐negative breast cancer

Abstract: The interaction between hypoxia and immune status has been confirmed in various cancer settings, and corresponding treatments have been investigated. However, reliable biomarkers are needed for individual treatment, so we sought to develop a novel scoring system based on hypoxia and immune status. Prognostic hypoxia-immune status-related signatures of patients with triple-negative breast cancer (TNBC) were identified in The Cancer Genome Atlas (TCGA) (N = 158), Molecular Taxonomy of Breast Cancer International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 65 publications
4
65
0
Order By: Relevance
“…The key markers of hypoxia (ALDOA, ENO1, LDHA, etc.) are highly expressed in the hypoxia high / immune low group, while a higher percentage of CD8+ T cells was observed in the hypoxia low /immune high group (40). In this case, both their and our results confirmed that there is a strong positive correlation between the hypoxia status of tumor and immunosuppression.…”
Section: Discussionsupporting
confidence: 83%
“…The key markers of hypoxia (ALDOA, ENO1, LDHA, etc.) are highly expressed in the hypoxia high / immune low group, while a higher percentage of CD8+ T cells was observed in the hypoxia low /immune high group (40). In this case, both their and our results confirmed that there is a strong positive correlation between the hypoxia status of tumor and immunosuppression.…”
Section: Discussionsupporting
confidence: 83%
“…Biological processes including apoptosis, hypoxia, mTORC1 signaling and myogenesis, and oncogenic features of EGFR and RAF were in proactivity to attribute to an inferior response. In fact, the potential triggers of distinct response to NCT remain undetermined, considering these findings to some extent enlighten the quest for improvement of efficacy, which were in accordance with the previous studies [34][35][36][37]. Current trials have exerted efforts and assess the efficacy of this kind of targeted therapies in TNBC [38,39], while these results were controversial and remained to be updated through randomized controlled trials with a large sample cohort.…”
Section: Discussionsupporting
confidence: 77%
“…Biological processes including apoptosis, hypoxia, mTORC1 signaling and myogenesis, and oncogenic features of EGFR and RAF were in proactivity to attribute to an inferior response. In fact, the potential triggers of distinct response to NCT remain undetermined, considering, these ndings to some extent enlighten the quest for improvement of e cacy, which were in accordance with the previous studies [24][25][26][27]. Current trials have exerted efforts and assess the e cacy of this kind of targeted therapies in TNBC [28,29], however, these results were controversial and remained to be updated through randomized controlled trials with a large sample cohort.…”
Section: Discussionsupporting
confidence: 77%